(untitled) (Diametros, 2020)
This paper explores the implications of Manfred Kuehn’s observation that Kant’s claim in Religion within the Boundaries of Mere Reason that the ethical community must be a community under God seems “a bit strained.” After clarifying Kant’s train of thought that results in his conception of the ethical community in the form of the “visible church,” the paper argues that the seemingly strong religious dimension may be misleading. If we understand the ethical community to be the development of the kingdom of ends in the Groundwork , it becomes apparent that Kant’s notion of God’s “sovereignty” over the ethical community is a shared sovereignty lodged in rationality and not in God’s own will. The “strain” that Kuehn senses thus suggests the potentially gratuitous nature of Kant’s references to God’s sovereignty over the ethical community. Despite the initial appearances, Kant’s account of the ethical community in the form of the visible church is, over the long term, closer to a secularizing move than to a robustly religious one.